PEMANFAATAN MEDIA GOOGLE CLASSROOM DALAM UPAYA MENUNJANG PEMBELAJARAN TEKNIK DASAR OTOMOTIF KELAS X SMK MA’ARIF 1 PIYUNGAN YOGYAKARTA - Aang Hardian (JURNAL VOKASI DEWANTARA (JVD), 2023)
This study aims to describe the effectiveness of the use of Google Classroom media in learning media, to find out the obstacles faced in the use of Google Classroom for teachers and students. Google Classroom is an internet- based service provided by Google as a learning system. Teachers and students who use this application can do online learning through computers and cell phones owned by each student which allows the creation of virtual world classrooms. This research is a qualitative descriptive study. This research was conducted at SMK Ma'arif 1 Piyungan Yogyakarta. Sources of information in this study consisted of class teachers, principals and students. Data collection techniques using observation, interviews, and documentation. The validity of the data was tested by increasing persistence and triangulation (source, technique, and time). The data analysis technique uses the Miles and Huberman model which consists of data collection (data collection), data reduction (data reduction), data display (data presentation), and conclusion drawing/verification (drawing conclusions). The results of this study indicate that the use of google classroom is quite effective and efficient. Effectiveness is seen from the creation and delivery of assignments and presentation of material, creating and organizing class assignments quickly, and being able to communicate directly with students without being limited by space and time, as well as taking advantage of time and being able to improve the quality of communication so that students can easily learn the material. given by the teacher.